Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1365-2168.1998.00905.x
|View full text |Cite
|
Sign up to set email alerts
|

Resympathectomy for palmar and axillary hyperhidrosis

Abstract: The main cause of primary sympathectomy failure was inadequate surgery, and recurrence of palmar or axillary hyperhidrosis was seldom caused by nerve regeneration. The key factor for preventing failed sympathectomy or recurrent palmar or axillary hyperhidrosis is a first-time sympathectomy that is both accurate and adequate. Most patients with recurrent symptoms can be cured by resympathectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…We agree with Hsu et al, who stated that the key factor for preventing failed or recurrent cases is a procedure that is accurate, adequate, and performed by a specialized team. 23 Another problem found in various case series was the degree of symptom recurrence. Gossot et al found a recurrence rate of 65% for axillary hyperhidrosis, 15 a result that was at variance from the 15% reported by Claes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We agree with Hsu et al, who stated that the key factor for preventing failed or recurrent cases is a procedure that is accurate, adequate, and performed by a specialized team. 23 Another problem found in various case series was the degree of symptom recurrence. Gossot et al found a recurrence rate of 65% for axillary hyperhidrosis, 15 a result that was at variance from the 15% reported by Claes.…”
Section: Discussionmentioning
confidence: 99%
“…Their mean age was 26.08 Ϯ 8.35 years (range, 13-54 years); 170 (61.6%) were female and 106 (38.4%) were male. Their mean body mass index (BMI) was 22.09 Ϯ 3.0 (range, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Almost all the patients were healthy, with nothing notable in their history or on physical examination, but 9 (3.2%) had a previous history of respiratory diseases.…”
Section: Methodsmentioning
confidence: 99%
“…[11,12] The optimal procedure, ablation (electrocautery) or sympathectomy (excision) has remained a controversy. Some surgeons prefer to ablate the ganglia because they opine that it is easier, requires a shorter operating time, leads to fewer cases of recurrence and Homer's syndrome, [12][13][14][15] our experience in this study equally indicates that thoracoscopic sympathectomy is a satisfactory and easy method for treating hyperhidrosis with acceptable operation time and complication rate with no failures necessitating the possibility of re-operating on the patients to achieve dry hands.…”
Section: Discussionmentioning
confidence: 60%
“…Failure of symptom resolution can be attributed to various causes such as mistaken identification of the sympathetic level, incomplete ablation, or accessory nerve pathways [6] (Kuntz fiber). Resympathectomy has been advocated and successfully performed for immediate failures and recurrence cases [17] if the surgeon acknowledges possible anatomic variations and can overcome the problems related to pleural adhesions [18].…”
Section: Discussionmentioning
confidence: 99%